The complete mitochondrial genome sequences of Japanese earthworms Metaphire hilgendorfi and Amynthas yunoshimensis (Clitellata: Megascolecidae) - Akira Seto; Hayato Endo; Yukio Minamiya; Masaru Matsuda (Mitochondrial DNA. Part B. Resources, 2021)
Many studies have reported the complete mitochondrial genome sequences of Chinese Megascolecidae earthworms, however, there have been no reports on sequences originating from Japanese Megascolecidae earthworms. In this study, we determined complete mitochondrial genome sequences of two Japanese earthworms belonging to the Pheretima complex within the Megascolecidae family. Metaphire hilgendorfi is one of the most common earthworms in Japan and Amynthas yunoshimensis was found to be morphologically similar to M. hilgendorfi. The complete mitochondrial genomes of M. hilgendorfi (15,186 bp; LC573968) and A. yunoshimensis (15,109 bp; LC573969) contained typical 13 protein coding genes, 22 tRNA genes, and 2 rRNA genes. The phylogenetic analysis revealed that these two species were sister species. Therefore, our findings will further contribute to phylogenetic and genetic diversity analyses of Megascolecidae earthworms.